2021
DOI: 10.3389/fphys.2021.639857
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopiazonic Acid-Induced Ca2+ Store Depletion Initiates Endothelium-Dependent Hyperpolarization-Mediated Vasorelaxation of Mesenteric Arteries in Healthy and Colitis Mice

Abstract: Purposes: Since the role of store-operated calcium entry (SOCE) in endothelium-dependent hyperpolarization (EDH)-mediated vasorelaxation of mesenteric arteries in health and colitis is not fully understood, cyclopiazonic acid (CPA), a specific inhibitor of the sarco(endo) plasmic reticulum calcium-ATPases (SERCA), was used as a SOCE activator to investigate its role in normal mice and its alteration in colitis mice.Methods: The changes in Ca2+ signaling in vascular endothelial cells (VEC) were examined by sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Animal studies addressing EDH-mediated relaxations revealed a well-defined production of cyclooxygenases and NO synthase inhibitors that are coupled with hyperpolarization of VSMCs located in the proximity of these molecular reactions. Some experimental studies have established the heterogeneous nature of EDH factors by reporting the specific characteristics relating to the different species and vascular beds of concern [ 53 , 54 , 55 ]. Greater production of epoxyeicosatrienoic acids, which constitute the fundamental metabolites of the arachidonic P450 epoxygenase sequential reactions were noted [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies addressing EDH-mediated relaxations revealed a well-defined production of cyclooxygenases and NO synthase inhibitors that are coupled with hyperpolarization of VSMCs located in the proximity of these molecular reactions. Some experimental studies have established the heterogeneous nature of EDH factors by reporting the specific characteristics relating to the different species and vascular beds of concern [ 53 , 54 , 55 ]. Greater production of epoxyeicosatrienoic acids, which constitute the fundamental metabolites of the arachidonic P450 epoxygenase sequential reactions were noted [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in stem cell population was observed with concentrations of SKF-96365 and YM-58483 that have been used to block the physiological effects of SOC [ 31 , 46 , 47 , 48 , 49 ]. As SKF-96365 and YM-58483 may also target other receptor channels (ROC), GSK-7975A, a more specific inhibitor of Orai-dependent SOCE was used [ 50 , 51 , 52 ]. The fact that GSK-7975A had also significant effects on GSC supports the idea that SOC play a key role in maintaining the GSC pool in GBM as they do in oral/oropharyngeal squamous cell carcinoma cancer stem cells and in liver cancer stem cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOCE can also be activated by the pharmacological depletion of the ER Ca 2+ by means of multiple drugs. The most common strategy to evoke SOCE in endothelial cells (and in circulating ECFCs) is represented by the blockade of Sarco-Endoplasmic Reticulum Ca 2+ (SERCA) activity with cyclopiazonic acid (CPA) [ 61 , 62 , 63 , 64 ], a mycotoxin and a fungal neurotoxin produced by the moulds Aspergillus and Penicillium and by thapsigargin [ 38 , 39 , 51 , 63 ], a plant-derived lactone, whereas 2,5-di-tert-butylhydroquinone (tBHQ) was mostly exploited in earlier studies [ 65 , 66 , 67 ]. The blockade of SERCA activity results in passive ER Ca 2+ efflux from leakage channels, whose molecular identity in endothelial cells remains to be unveiled [ 68 ].…”
Section: How To Activate Endothelial Soce: Physiological Vs Pharmacol...mentioning
confidence: 99%